Integrasi Self-Efficacy pada Pembelajaran Matematika Berbasis Team-Based Learning (TBL) - Astiswijaya, Nike; Turmudi, Turmudi; Kusnandi, Kusnandi; Dadang Juandi, Dadang Juandi (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study is a conceptual review that aims to explain how self-efficacy is integrated into mathematics learning based on Team-Based Learning (TBL). In the initial stage, researchers found 120 articles. After screening, 15 articles were selected that were relevant and in line with the research focus. The synthesis results showed that the integration of self-efficacy and TBL created a mutually reinforcing cycle. The TBL structure was proven to provide space for the formation of four main sources of self-efficacy (Bandura, 1997), namely mastery experience, vicarious experience, verbal persuasion, and affective states. The integration of the two creates a reciprocal relationship: high self-efficacy makes students more confident and persistent in facing challenges, while the collaborative and supportive TBL environment strengthens students' self-efficacy. TBL is not just a learning strategy, but also a space for students to develop confidence in learning mathematics.   Keywords: Self-efficacy, Team-Based Learning, Mathematics Learning, Collaborative Learning, Higher-Order Thinking Skills